Pengaruh Intellectual Capital dan Diversity Gender terhadap Financial Distress Dimoderasi oleh Firm Size - Amanda Putri Ramadanty; Khomsiyah Khomsiyah (Politeknik Ganesha Medan, 2022)
The study aimed to investigate the effect of intellectual capital and gender diversity on financial distress as measured by Zmijewski where firm size was as moderating variable. Population involved was that the company properties and real estate listed on the Indonesia Stock Exchange in the period of 2020 until 2021, 130 companies were as the population and the samples were chosen by using purposive sampling. The samples that met the criterion were 100 companies. The hypotheses were investigated by using Moderated Regression Analysis. The results revealed that intellectual capital has a negative effect on financial distress, gender diversity had a positive effect on financial distress. Firm size as moderation strengthens the relationship of intellectual capital and firm size as moderation weakens the relationship gender diversity to financial distress.Companies can pay attention to factors outside the financial statements by increasing intellectual capital in terms of resources, so that the company is able to organize financial performance well so as to avoid financial distress. In addition, the factor of gender diversity as a determinant of the decision making of the board of directors is based on gender. This has an effect on optimal and dynamic decision making. So as to improve the Company's performance and minimize the occurrence of financial distress.